Fused‐ring induced end‐on orientation in conjugated molecular dyads toward efficient single‐component organic solar cells. Issue 2 (12th October 2022) - Xia, Dongdong; Zhou, Shengxi; Tan, Wen Liang; Karuthedath, Safakath; Xiao, Chengyi; Zhao, Chaowei; Laquai, Frédéric; McNeill, Christopher R.; Li, Weiwei
Abstract: The molecular orientations of conjugated materials on the substrate mainly include edge‐on, face‐on, and end‐on. Edge‐on and face‐on orientations have been widely observed, while end‐on orientation has been rarely reported. Since in organic solar cells (OSCs) charge transport is along the vertical direction, end‐on orientation with conjugated backbones perpendicular to the substrate is recognized as the ideal microstructure for OSCs. In this work, we for the first time obtained the preferential end‐on orientation in a conjugated molecular dyad that contains a conjugated backbone as donor and perylene bisimide side units as acceptor. This was realized by introducing a fused‐ring structure to replace linear terthiophenes with conjugated backbones, yielding F‐MDPBI and L‐MDPBI respectively. Surprisingly, a shifting trend of the molecular orientation from dominating edge‐on in L‐MDPBI to preferential end‐on in F‐MDPBI was observed. As a consequence, vertical charge carrier mobilities in F‐MDPBI are one order of magnitude higher than those with preferential edge‐on orientation, so single‐component OSCs based on this molecular dyad as a single photoactive layer provided a power conversion efficiency of 4.89% compared to 1.70% based on L‐MDPBI with preferential edge‐on orientation. Abstract : In this work, a new strategy to design molecular dyads by using a fused‐ring design has been established, which can enable the molecular dyads to have end‐on orientation, higher charge carrier mobilities, and better crystallinity, so that the fill factors approaching 0.60 and power conversion efficiencies of 4.89% can be achieved.